Trade openness and economic growth: a causality test in panel perspective - Idris, Jamilah; Yusop, Zulkornain; Habibullah, Muzafar Shah (Universiti Malaysia Sarawak, 2016)
Openness to trade has been one of the primary drivers stimulating growth.The goal of this particular study is to investigate the relationship between trade openness and economic growth in 87 selected countries which includes both Organizations for Economic Co-operation and Development (OECD) and developing countries for 1977–2011 periods.We used two measures of trade openness i.e. the ratio of trade openness (TO) typically spoke by exports plus imports in nominal value divided by GDP (nominal)which is commonly used in the literature,and trade openness in real(RO)which is defined as the sum of imports and exports in US$ relative to GDP in purchasing power parity US$ (real GDP). An empirical studywas conducted to determine the causal relationship between trade openness and growth in a panel perspective.We used a dynamic panel data estimation method i.e. the general method of moments(GMM). The empirical results reveal a bidirectional causal relationship for both developing and OECD countries.Our finding is consistent with the endogenous theory that increased openness leads to higher growth, which thus prompts expanded openness.